Integridade para além da jurisdição: uma análise crítica da interpretação jurídica no âmbito da atividade policial - Zanotti, Bruno Taufner (2018)
The thesis seeks a critical reflection about the theoretical and pragmatic assumptions of the task of interpreting the Law by the Chief of Investigation to administrate the Civil Police and to conduct the police investigation. The Democratic State of Law demands a new perspective for the justification of coercive power beyond the idea of discretionary, since the authority attributed to someone does not in itself represent a sufficient rational justification for legitimizing the use of power. In the light of Law as integrity, the thesis seeks not only to overcome the problems of this positivism, but to demonstrate that a rational foundation of each decision gains values and rights in a way that can show the community from its historicity and from the best point of view of political morality. In order to integrate the sources of research and to deepen the study of the subject, a hermeneutical approach is used, as well as empirical research of a quantitative-qualitative nature regarding the administrative activity within the scope of the Judicial Police. Based on the study and the analysis of the results, some conclusions are reached. 1. Legal Positivism has structural problems regarding the legitimacy of the decision and the understanding of the proper functioning of legal principles, especially in the context of what has been labeled ―Brazilian Legal Positivism‖. 2. Understanding the decision-making assumptions appropriate to the Democratic State of Law, will give the Chief of Investigation a special responsibility to administrate the Civil Police and to conduct the police investigation. 3. The new perception of how the Civil Police should work demands overcoming the classification of administrative acts in tied and discretionary, new reading of the principle of legality and new understanding of the principle of supremacy of public interest. 4. The understanding the idea of Law as integrity, even in the administrative-police activity, has important consequences for the police investigation, allowing the recognition of the investigated as a human rights holder, as well as to attribute to the police investigation a purpose that goes beyond providing just cause for criminal action.